Impact of Gender-Based Violence on Community Development: Case Study of Rumonge Commune (Burundi) - Alexis Ndabarushimana; Gilbert Mfisumukiza (European Scientific Journal, ESJ, 2022)
Gender-based violence (GBV) is a global problem that affectswomen and girls of all races, colors, and creeds. It occurs across all socioeconomic and cultural backgrounds, and in many societies, including Burundidespite different international, regional, and national instruments ratified toprotect women against GBV and its effects. This study conducted with 96individuals selected using Alain Bouchard’s technic highlights the impact ofgender-based violence (GBV) on community development and provides somesuggestions for action in remedy to gender-based violence persistence forcommunity development. It specifically shows the reasons behind thepersistence of gender-based violence in Rumonge Commune and itsimplications on the bad living conditions of families. To achieve this, we optedfor qualitative approaches with the use of the interview guide and quantitativewith the use of a questionnaire administered directly to heads of householdsdistributed in 6 zones of Rumonge Commune. The study found that the reasonsbehind the persistence of GBV in Rumonge are fundamentally linked toBurundian culture and tradition that structure how people have to behave and live in society. In view of the impact of GBV, identified as a constraint toindividual and societal development, this article highlights a set of activitiesto be done to reduce GBV. These include community dialogues around lawsregarding families and development; education and awareness of the impactsand ways to prevent it for community development. Perpetrators must also beproperly prosecuted and victims provided with all the needed resources fortreatment and judicial processes.